Red River barrier and Pleistocene climatic fluctuations shaped the genetic structure ofMicrohyla fissipescomplex (Anura: Microhylidae) in southern China and Indochina - Zhi-Yong Yuan; Chatmongkon Suwannapoom; Yan Fang; Nikolay A. Poyarkov; Sang Ngoc Nguyen; Hong-Man Chen; Siriwadee Chomdej; Robert W. Murphy; Jing Che (2016)
South China and Indochina host striking species diversity and endemism. Complex tectonic and climatic evolutions appear to be the main drivers of the biogeographic patterns. In this study, based on the geologic history of this region, we test 2 hypotheses using the evolutionary history of Microhyla fissipes species complex. Using DNA sequence data from both mitochondrial and nuclear genes, we first test the hypothesis that the Red River is a barrier to gene flow and dispersal. Second, we test the hypothesis that Pleistocene climatic cycling affected the genetic structure and population history of these frogs. We detect 2 major genetic splits that associate with the Red River. Time estimation suggests that late Miocene tectonic movement associated with the Red River drove their diversification. Species distribution modeling (SDM) resolves signiﬁcant ecological differences between sides of the Red River. Thus, ecological divergence also probably promoted and maintained the diversification. Genogeography, historical demography, and SDM associate patterns in southern China with climate changes of the last glacial maximum (LGM), but not Indochina. Differences in geography and climate between the 2 areas best explain the discovery. Responses to the Pleistocene glacial-interglacial cycling vary among species and regions.